The role of packaging to influence purchase intention of smes product in pasaman regency - Yasri, Yasri; Budiarti, Astra Prima (Jurnal Aplikasi IPTEK Indonesia, 2021)
This study aims to analyze the effect of the benefits of product packaging on the interest in purchasing MSME products in Pasaman Regency. The population of this research are consumers of MSME products in three villages in Pasaman Regency. A total of 255 samples were selected by purposive sampling technique. This study uses the Structural Equation Model (SEM) technique using SmartPLS 3 as a data analysis tool. The results showed that the benefits of packaging (Hedonic benefit of packaging and Utilitarian benefit of packaging influenced consumer buying interest in MSME food products in Pasaman Regency.